Turk Arch Pediatrics 2023
DOI: 10.5152/turkarchpediatr.2023.23194
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder in 2023: A Challenge Still Open

Abstract: In this paper, we provide an update on autism spectrum disorder (ASD), including epidemiology, etiopathogenesis, clinical presentation, instrumental investigations, early signs, onset patterns, neuropsychological hypotheses, treatments, and long-term outcome. The prevalence of this condition has increased enormously over the last few decades. This increase prompted a search for possible environmental factors whose effects would add up to a genetic predisposition leading to the development of autism. But the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 45 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Oppositional defiant disorder is one of the many neuropsychiatric comorbidities reported in individuals with autism spectrum disorder (ASD), along with intellectual disability, attention-deficit/hyperactivity disorder (ADHD), anxiety disorders, and depressive disorders. 2 , 3 Depending on the studies available in the literature, the recurrence of ODD reported in children and adolescents with ASD varies greatly from approximately 7% to 75%, most likely due to the different methodologies used. However, according to most studies, it is higher than 20%.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Oppositional defiant disorder is one of the many neuropsychiatric comorbidities reported in individuals with autism spectrum disorder (ASD), along with intellectual disability, attention-deficit/hyperactivity disorder (ADHD), anxiety disorders, and depressive disorders. 2 , 3 Depending on the studies available in the literature, the recurrence of ODD reported in children and adolescents with ASD varies greatly from approximately 7% to 75%, most likely due to the different methodologies used. However, according to most studies, it is higher than 20%.…”
mentioning
confidence: 99%
“…Indeed, the symptoms that characterize ODD could at least partly find an explanation in the context of the complex clinical picture presented by individuals with ASD. For example, when a child with ASD perceives very unpleasant sensations (e.g., in a crowded and noisy environment or when faced with highly disturbing visual stimuli) due to his/her own sensory abnormalities (so frequent in these patients), 3 , 8 he/she may present intense and stubborn manifestations of rejection toward the situation experienced, associated with apparently inexplicable reactions of anger toward the persons around him/her. These symptoms can mimic the clinical picture of ODD, particularly in younger children who are unable to communicate verbally.…”
mentioning
confidence: 99%
See 1 more Smart Citation